2009
DOI: 10.1590/s1677-55382009000400011
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal therapy for painful bladder syndrome / interstitial cystitis: pilot study combining behavioral, pharmacologic, and endoscopic therapies

Abstract: Purpose:We evaluated the effectiveness of combining behavioral therapy, pharmacologic therapy and endoscopic hydrodistension for treating painful bladder syndrome / interstitial cystitis (PBS/IC). Materials and Methods: Twenty-five patients with PBS/IC were prospectively enrolled in a pilot multimodal behavioral, pharmacologic and endoscopic treatment protocol. Behavioral modification included diet recommendations, fluid restriction to 64 oz. /day, progressive timed voiding and Kegel exercises. Oral pharmacolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Despite dietary modifications being considered standard care for this population [ 6 , 19 , 20 , 21 , 22 , 23 ], there are only three published clinical trials that have investigated the efficacy of dietary changes for helping to manage IC/BPS symptoms [ 43 , 44 , 45 ]. A pilot study ( n = 25) conducted by Hanley et al included dietary modification as part of a multimodal intervention (behavioral, pharmacologic, and endoscopic) [ 43 ]. In addition to fluid restrictions, participants restricted acidic foods and those high in arylalkylamines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite dietary modifications being considered standard care for this population [ 6 , 19 , 20 , 21 , 22 , 23 ], there are only three published clinical trials that have investigated the efficacy of dietary changes for helping to manage IC/BPS symptoms [ 43 , 44 , 45 ]. A pilot study ( n = 25) conducted by Hanley et al included dietary modification as part of a multimodal intervention (behavioral, pharmacologic, and endoscopic) [ 43 ]. In addition to fluid restrictions, participants restricted acidic foods and those high in arylalkylamines.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to fluid restrictions, participants restricted acidic foods and those high in arylalkylamines. The researchers, however, reported no discrete findings on the influence of the dietary modifications [ 43 ]. A double-blind, placebo-controlled trial ( n = 30) evaluated the influence of caffeine on the exacerbation of IC/BPS symptomology.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, combination therapy may improve the efficacy of IC treatment as several different causes of IC have been suggested. Regarding suplatast tosilate, a couple of combination therapies can be suggested: (i) combination of oral suplatast tosilate and hydrodistention (referred from Study A and a previous report on the efficacy of a combination of behavioral and pharmacologic interventions and hydrodistention in female IC patients); and (ii) combination of oral anticholinergic drugs and suplatast tosilate to treat the damaged bladder internally, as well as externally. In IC, inflammation invades from the bladder epithelium (internal side) to the detrusor where, as in OAB, the neural excitation occurs from the external side of the bladder to the epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the regulation of diet and fluids intake reduces constipation and normalizes the frequency of urination [ 18 , 19 ]. Pelvic floor relaxation exercises (placing knees against the chest, reclining with spread legs, or squatting) and bladder training have also been shown to improve symptoms increasing intervals between urinations and void volume [ 20 , 21 ]. Although all of these approaches are able to improve IC/BPS, the psychological support with appropriate coping strategies and stress management has a key role in these women.…”
Section: Conservative Treatmentmentioning
confidence: 99%
“…Among them, cimetidine and hydroxyzine were the most investigated so far. Cimetidine (H2 antagonist) was related to a significant improvement of suprapubic pain and nocturia as compared to placebo in a randomized controlled trial, although the histology of the bladder biopses was reported unchanged [ 21 , 50 , 51 ]. Hydroxyzine is a H1 antagonist with anticholinergic activity, that reported in different observational studies an improvement of symptoms up to the 90% of treated patients, with sedation representing the primary side effect.…”
Section: Oral Medicationsmentioning
confidence: 99%